PARTISIPASI DAN REPRESENTASI PEREMPUAN DALAM PENYELENGGARAAN PEMILU - Bintari, Antik (Jurnal Keadilan Pemilu, 2021)
Realizing equal access for women and men to be actively involved in politics and the political decision making process still requires special attention from stakeholders in various countries in the world. One of the crucial problems is that there is still an imbalance in the composition of men and women in representative institutions. So far, the focus of women's rights in politics has always looked at the representation of women as candidates for legislative, executive, and even management members in political parties and very rarely discusses women's representation as election organizers such as in the General Election Commission (KPU), Election Supervisory Agency (BAWASLU), as well as the Election Organizing Ethics Council (DKPP). Women's political rights are essentially not only about the presence of women in political parties and parliaments but in the whole process of organizing elections, including election monitoring. Professional election management institutions are one of the determinants of democratic elections. The opening of access and opportunities for women to become members of the election administration is one of the indicators used to determine whether the election management body has democratically.